Effect of Antihyperglycemic Agents on Hemoglobin A1c Level in Type 2 Diabetes Mellitus Patients - Kamila, Tasya; Dewi, Vycke Yunivita Kusumah; Miftahurachman, Miftahurachman (Althea Medical Journal, 2018)
Background: Type 2 diabetes mellitus (T2DM) patients require continuous lifelong attention to pharmacotherapy to achieve and maintain optimal glucose control, which can be monitored through measuring HbA1c. This study aimed to see the comparrison of HbA1c levels before and after a minimum of two months use of antihyperglycemic agents in patients with T2DM.Methods: This analytical cross-sectionalÂ  study used medical records of patients with T2DM in the center of outpatient medical records at the Department of Clinical Pathology, Dr. Hasan Sadikin General Hospital, inÂ  2013. Sampling was conducted using consecutive sampling technique. The data analysis used the paired t-test and Wilcoxon test for not normal data distribution.Results: Before and after a minimum of two months useÂ  of antihyperglycemic agents, HbA1c concentration was 7.15% (6.1â12.2) and 7.3% (5.9â11.9) respectively. Statistically, the difference of HbA1c concentration of T2DM patients between those periodÂ  was not significant (0.15%; p=0,812). Mean HbA1c concentration was found with greatest decrease in patients treated with sulfonylurea (2.25%), followed by insulin (0.1%). There were increases in mean HbA1c concentration in patients treated with metformin (0.05%), metformin+insulin (1.1%), sulfonylurea +metformin (0.6%), sulfonylurea+alpha-glucosidase inhibitor (1.1%), and sulfonylurea + metformin + alpha-glucosidase inhibitor (0.05%).Conclusions: There is no significant difference of HbA1c levels before and after two months to two years use of antihyperglycemic agents in T2DM patients. This result showed the importance of comprehensiveness in T2DM therapy. The therapy should not merely consist of antihyperglycemic medication alone, but also physical exercise, lifestyle modification, and diet control.